Konstruksi Alat Ukur Impulsivitas Pada Narapidana - Usman, Muh. Yusrifal; Widyastuti, Widyastuti; Ridfah, Ahmad (Polteknik Ilmu Pemasyarakatan, 2024)
The construction of an impulsivity measurement scale is one of the methods that can be used to assess the impulsive tendencies of prisoners in Correctional Institutions (LAPAS). This is because impulsivity is one of the factors that contribute to the formation of various behavioral and psychological problems in prisoners during their prison term. This study aims to produce a new impulsivity scale based on the characteristics of the impulsive behavior of prisoners. The sampling technique used is quota sampling. This research involved 227 respondents in study 1 and 375 respondents in study 2. The data analysis methods used were item response theory (IRT), exploratory factor analysis (EFA), and confirmatory factor analysis (CFA). The results of the development of the impulsivity scale produced 21 items with six factors forming impulsive behavior. The construct reliability of the six factors ranged from 0.74 - 0.84 and AVE ranged from 0.45 - 0.59. The goodness of fit results also show that the measurement model is acceptable. Keywords: Confirmatory factor analysis, exploratory factor analysis, impulsivity, item response theory, reliability